Grammar Material Training to Improve Communication in Entrepreneurial Projects for Elementary and High School Students in Cilawu District, Garut - Adiansyah, Adi; Isnawati, Isnawati; Soni, Mohammad (Fakultas Kewirausahaan Universitas Garut, 2025)
This problem arises from the lack of specific training integrating language and communication aspects in the context of entrepreneurship. The lack of explicit instruction on appropriate, logical, and persuasive language use results in students lacking confidence in conveying their creative ideas. This method was chosen because it aligns with the objectives of community service activities, which are direct and participatory interventions, and allows for continuous reflection and improvement based on the results of the activities. Grammar training is effective as a medium for improving students' communication competencies in entrepreneurial projects, while simultaneously supporting the development of creative, communicative, and self-confident character traits at the elementary and secondary levels in Cilawu District. Teachers are encouraged to act as facilitators, assisting students in honing their communication skills, rather than simply as language instructors. Therefore, Grammar is effective as a medium for improving students' communication competencies in entrepreneurial projects, while simultaneously supporting the development of creative, communicative, and self-confident character traits at the elementary and secondary levels in Cilawu District.